A Dynamic Model for Road Gasoline and Diesel Consumption: An Application for Spanish Regions - González Marrero, Rosa Marina; Lorenzo-AlegrÃa, Roza M.; Marrero, Gustavo A. (International Journal of Energy Economics and Policy, 2012)
This paper analyzes the factors explaining the aggregate fuel consumption for road transport in Spain in a dynamic panel data framework. Three features on this study are the use of a balanced panel using regional data, the distinction between gasoline and diesel and the specification of a dynamic panel data (DPD) model and estimate it by system Generalized Methods of Moments (GMM). Our results show that most explanatory variables are significant in explaining the evolution of gasoline consumption, while diesel consumption is found to be independent of most of these factors. The differences between the markets of the gasoline (most for passenger transport use) and the diesel (passenger and freight transport are important) could explain the results for the diesel model. Moreover, the intensive dieselization process that has taken place in Spain over the last decade, which has resulted in diesel consumption being exposed to factors - i.e., regulatory - which are not of a strictly economic nature. This finding highlights the need to consider different explanatory variables and models for gasoline and diesel consumption, and to go further in the research. Finally, we find that traditional estimation procedures, such as fixed and random effect estimators, produce important differences with respect to system-GMM, which may even change policy recommendations. Keywords: Fuel consumption; Road transport; Dynamic Panel Data model; GMM estimates. JEL Classifications: R41; O13; O56